Triple-play services using random diagonal code for spectral amplitude coding OCDMA systems - Hilal Adnan, Fadhil; Syed Alwee Aljunid, Syed Junid, Prof. Madya; R. Badlishah, Ahmad (Fachverlag Schiele and Schoen GmbH, 2010)
Link to publisher's homepage at http://www.schiele-schoen.de/